Efeito do potencial matricial e da época de plantio na produtividade de dois cultivares de feijão-de-corda, Vigna unguiculata, (L.) Walp., no Vale do Curu sob regime de irrigação - Bezerra, Francisco Marcus Lima (1985)
The present work was undertaken during 1983/84 at the "Vale do Curu" Experimental Station, Pentecoste-CE, in an Aluvial soil, to study the behavior of two varieties of cow-pea (Vigna unguiculata (L.) Walp) (Pitiúba and João Paulo II), eight days of sowing (28/07; 12 and 27/08; 11 and 25/09; 10 and 25/10; and 11/11/1983), under two water stress conditions (- 0,40 and - 0,70 atm). [...]